Armillaria mellea Mycelia Alleviate PM2.5-Induced Pulmonary Inflammation in Murine Models - Yi-Ping Huang; Yu-Tsen Huang; Hui-Yu Wu; Li-Fang Chou; You-Shan Tsai; Yih-Min Jiang; Wan-Ping Chen; Ting-Wei Lin; Chin-Chu Chen; Chih-Ho Lai (MDPI AG, 2024)
Particulate matter (PM) with an aerodynamic diameter of ≤2.5 μm (PM2.5) significantly contributes to various disease-related respiratory inflammations. Armillaria mellea, recognized for its medicinal properties, could alleviate these respiratory ailments. However, its efficacy against PM2.5-induced inflammation remains elusive. In this study, we investigated whether A. mellea mycelia could mitigate PM2.5-induced respiratory inflammation and assessed the underlying mechanisms. Our results showed that A. mellea mycelia significantly reduced PM2.5-induced nitric oxide (NO) production and nuclear factor (NF)-κB activation in macrophages. Furthermore, A. mellea mycelia suppressed the expression of inflammatory mediators, indicating their potent antioxidant and anti-inflammatory properties. In murine models, A. mellea mycelia mitigated PM2.5-induced lung inflammation and cytokine secretion, restoring lung inflammatory status. Our results highlight the potential of A. mellea mycelia to treat PM2.5-induced respiratory inflammation. The antioxidant and anti-inflammatory effects of A. mellea mycelia demonstrated in vitro and in vivo hold promising potential for developing respiratory health improvement interventions upon PM2.5 exposure.